PENGELOLAAN PEMBELAJARAN MATEMATIKA KONTEKSTUAL DI SEKOLAH MENENGAH KEJURUAN - Budiyati, Sri; Sutama, Sutama; Narimo, Sabar (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The  research  objective  is  to  describe  contextual-based  math  learning management,  which  includes  planning,  implementation  and  evaluation  as  well  as describe  the  constraints  of  experienced  math  teachers  in  the  implementation  of contextual-based mathematics  learning at SMK Negeri 3 Klaten. The research method used  is  descriptive  qualitative  research,  research  data  on  the  implementation  of contextual learning was collected using interviews, observation and documentation. It is concluded in conclusion: (1) Planning learning early in the learning of mathematics held by preparing syllabi and lesson plans, (2) implementation of contextual learning mathematics in SMK Negeri 3 Klaten is not optimal, (3) Ratings are not only assess the  final  outcome  but  also  to  assess  the  process.  Implementation  of  learning mathematics is not optimal constrained by: (1) Teachers do not fully understand and master the contextual learning, (2) Teachers difficulties when learning material linked with the life situation that is already known by the student, (3) Teachers still tend to use the lecture method, although teachers have learned a variety of learning methods.Kata Kunci: contextual, learning, management